On the rationality of some moduli spaces related to pointed trigonal curves - Casnati, G. (MATHEMATICA SCANDINAVICA, 2012)
For each g1, let T_g,nM_g,n be the locus of points corresponding to curves carrying a base-point-free g^1_3. Here we give a proof that T_g,n is rational if g4 and 1n2g+7.